Analysis of unreinforced and reinforced tubular T-joints structures with open source finite element software. Issue 4 (16th February 2023) - Saberi, Sina; Fantuzzi, Nicholas
Abstract: Tubular Joints play quite a vital role in most marine structures. It is obvious that having full control about the capacity and strength of tubular joints would be very worthy to have good knowledge about the total performance of the structure. In recent years, the application of the finite element method has become very popular in the analyses of different types of welded circular tubular joints and many commercial and open-source FE systems have been profoundly involved in these regards. Most of these software shares so much in common that it is difficult to differentiate them. This study was performed to investigate and report the usefulness of the open-source software programs in implementing finite element modeling for design applications. In this regard, with aid of the open-source finite element package Code_Aster and its user-friendly interface Salome-Meca, the behavior of reinforced and unreinforced T-joint specimens subjected to axial brace load with different geometry and material property has been studied. In addition, different types of shell and solid finite elements with various mesh densities are considered in this research. In order to overlap the outcomes, the numerical results of this research are present in terms of load-ovalization curves along with the results of other references. Due to mesh sizes and the element types, 144 different simulations have been performed on 12 different specimens. The results show that Code_Aster can satisfactorily predict the nonlinear static behavior of reinforced and unreinforced joints under both tension and compression load. Hence, Code_Aster can be used as a reliable tool for the evaluation and analysis and design of complex offshore joints.